Statistically verified methods for determining predictors of development of arterial hypertension depending on endothelial nitric oxide synthase T786C gene promoter polymorphism using lipid profile indicators - Pidruchna Svitlana; Shmanko Volodimir; Hnizdyukh Roman; Sverstiuk Andrii; Lykhatskyy Petro; Kuzmak Iryna; Yaroshenko Tetyana; Bandas Iryna; Vasylyshyn Nadya; Ostrivka Oksana; Mudra Alla; Palytsia Lylya; et al. (Endocrine Regulations)
Objective. Polymorphism investigation of T786C gene promoter of endothelial nitric oxide synthase (eNOS/NOS3) in the arterial hypertension is a promising field for determining the relationship between heredity, hypertension, and dyslipidemia, which still remains controversial. The purpose of the study was to investigate the lipid profile, which depends on the NOS3 T786C gene promotor region polymorphism in patients with arterial hypertension.